Intersectionality in residental solar adoption: Examining socio-demographics, racial diversity, geography, solar suitability, and policy in the United States - Gerald Jones; Chien-Fei Chen; Wei-An Chen; Lillian Lovingood; Xueping Li (Energy Strategy Reviews)
Residential rooftop photovoltaic (RPV) solar power offers a dual benefit: it reduces energy bills and helps combat climate change. Yet, the widespread adoption of RPV is influenced by multifaceted factors. This research delves into five key dimensions: socio-demographic and household characteristics, spatial location and racial diversity, solar suitability and rooftop potential, energy pricing and consumption behavior, and policy and incentives. Through an analysis of U.S. census tract data, this study covers residential solar adoption across all U.S. states, encompassing regions with high solar radiation and the top 5% of adoption areas. Regression models reveal that the most robust predictors of RPV adoption are policy incentives and the potential for energy cost savings. This result underscores an interactive relationship involving electricity expenses, solar radiation, and suitability. The interplay of income and education significantly contributes to a higher adoption rate. Surprisingly, the interaction between energy pricing and consumption inhibits solar adoption in areas with substantial energy use. Longer commutes negatively impact adoption, resulting in lower rates in rural areas. However, diverse populations in these regions lead to heightened adoption rates. These findings emphasize the necessity of scrutinizing interactive effects and suggest actionable policy recommendations to facilitate the widespread adoption of RPV technology, particularly in underserved and diverse communities.